Serological testing for SARS‐CoV‐2 antibodies in clinical practice: A comparative diagnostic accuracy study. Issue 7 (11th January 2022) - Horn, Michael P.; Jonsdottir, Hulda R.; Brigger, Daniel; Damonti, Lauro; Suter‐Riniker, Franziska; Endrich, Olga; Froehlich, Tanja K.; Fiedler, Martin; Largiadèr, Carlo R.; Marschall, Jonas; Weber, Benjamin; Eggel, Alexander; et al.
Abstract: Background: Serological tests are a powerful tool in the monitoring of infectious diseases and the detection of host immunity. However, manufacturers often provide diagnostic accuracy data generated through biased studies, and the performance in clinical practice is essentially unclear. Objectives: We aimed to determine the diagnostic accuracy of various serological testing strategies for (a) identification of patients with previous coronavirus disease‐2019 (COVID‐19) and (b) prediction of neutralizing antibodies against SARS‐CoV‐2 in real‐life clinical settings. Methods: We prospectively included 2573 consecutive health‐care workers and 1085 inpatients with suspected or possible previous COVID‐19 at a Swiss University Hospital. Various serological immunoassays based on different analytical techniques (enzyme‐linked immunosorbent assays, ELISA; chemiluminescence immunoassay, CLIA; electrochemiluminescence immunoassay, ECLIA; and lateral flow immunoassay, LFI), epitopes of SARS‐CoV‐2 (nucleocapsid, N; receptor‐binding domain, RBD; extended RBD, RBD+; S1 or S2 domain of the spike [S] protein, S1/S2), and antibody subtypes (IgG, pan‐Ig) were conducted. A positive real‐time PCR test from a nasopharyngeal swab was defined as previous COVID‐19. Neutralization assays with live SARS‐CoV‐2 were performed in a subgroup of patients to assess neutralization activity ( n  = 201). Results: The sensitivity to detect patients with previous COVID‐19 was ≥85% in anti‐N ECLIA (86.8%) and anti‐S1 ELISA (86.2%). Sensitivity was 84.7% in anti‐S1/S2 CLIA, 84.0% in anti‐RBD+LFI, 81.0% in anti‐N CLIA, 79.2% in anti‐RBD ELISA, and 65.6% in anti‐N ELISA. The specificity was 98.4% in anti‐N ECLIA, 98.3% in anti‐N CLIA, 98.2% in anti‐S1 ELISA, 97.7% in anti‐N ELISA, 97.6% in anti‐S1/S2 CLIA, 97.2% in anti‐RBD ELISA, and 96.1% in anti‐RBD+LFI. The sensitivity to detect neutralizing antibodies was ≥85% in anti‐S1 ELISA (92.7%), anti‐N ECLIA (91.7%), anti‐S1/S2 CLIA (90.3%), anti‐RBD+LFI (87.9%), and anti‐RBD ELISA (85.8%). Sensitivity was 84.1% in anti‐N CLIA and 66.2% in anti‐N ELISA. The specificity was ≥97% in anti‐N CLIA (100%), anti‐S1/S2 CLIA (97.7%), and anti‐RBD+LFI (97.9%). Specificity was 95.9% in anti‐RBD ELISA, 93.0% in anti‐N ECLIA, 92% in anti‐S1 ELISA, and 65.3% in anti‐N ELISA. Diagnostic accuracy measures were consistent among subgroups. Conclusions: The diagnostic accuracy of serological tests for SARS‐CoV‐2 antibodies varied remarkably in clinical practice, and the sensitivity to identify patients with previous COVID‐19 deviated substantially from the manufacturer's specifications. The data presented here should be considered when using such tests to estimate the infection burden within a specific population and determine the likelihood of protection against re‐infection. Abstract : This large prospective cross‐sectional study determines the diagnostic accuracy of various serological testing strategies for identification of patients with previous COVID‐19 and prediction of neutralizing antibodies against SARS‐CoV‐2 in real‐life clinical settings. The diagnostic accuracy in detecting patients with previous COVID‐19 was high in anti‐N ECLIA and anti‐S1 ELISA (sensitivity ≥85%; specificity ≥97%). The accuracy in detecting neutralizing antibodies was high in anti‐S1/S2 CLIA and anti‐RBD+LFI (sensitivity ≥85%; specificity ≥97%).Abbreviations: CLIA, chemiluminescence immunoassay; COVID‐19, coronavirus disease 2019; ECLIA, electrochemiluminescence immunoassay; ELISA, enzyme‐linked immunosorbent assay; LFI, lateral flow immunoassay; N, nucleoprotein; RBD, receptor‐binding domain of the SARS‐CoV‐2 spike glycoprotein; RBD+, extended receptor‐binding domain of the SARS‐ CoV‐2 spike glycoprotein; SARS‐CoV‐2, severe acute respiratory syndrome coronavirus 2; S1/2, domain 1 or 2 of the SARS‐CoV‐2 spike glycoprotein